Peran Koperasi Siswa dalam Pengembangan Kemampuan Kewirausahaan - Mirlana, Dendy Eta; Nuryantini, Nanik (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2024)
This study aims to identify the role of student cooperatives in developing entrepreneurial skills at SMK Negeri 1 Jenangan Ponorogo. The research employs a qualitative approach with a descriptive method. Data were collected from various sources, including the school principal, student cooperative mentors, and students serving as cooperative managers. Data collection techniques included observation, documentation, and interviews. Data analysis was conducted descriptively and qualitatively with an inductive approach, and the validity of the data was verified through source triangulation and member checking. The findings indicate that: (1) the student cooperative at SMK Negeri 1 Jenangan Ponorogo directly involves students in its management; (2) the student cooperative plays a crucial role in shaping students' entrepreneurial character through various programs and observed character changes; (3) the implementation of the student cooperative runs well, with students given the responsibility to manage the cooperative as a means of training entrepreneurial skills.